PERAN CUSTOMER SATISFACTION MEMEDIASI PENGARUH EXPERIENTIAL MARKETING TERHADAP REPEAT PURCHASE PADA MANGSI COFFEE DI DENPASAR - Wijaya, Putu Eka Surya Ananta; Suparna, Gede (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
Mangsi Coffee is a cafe that provides foods and beverages that has its own characteristics compared from other cafes and restaurants. The purpose of this study is to determine the role of customer satisfaction which mediates the influence of experiential marketing towards repeat purchase at Mangsi Coffee in Denpasar. The research sampling method used in this research is non probability sampling by applying purposive sampling technique. This study uses primary data which was collected using a questionnaire as a research instrument that wasspread to the respondents. Respondents are Mangsi Coffee costumers who have made purchase at least twice. The number of the respondents who participated for the analysis were 140 respondents. The analysis technique used was path analysis. This study found that experiential marketing is positively and significantly impact on customer satisfaction. Customer satisfaction is positively and significantly impact on repeat purchase. Experiential marketing is positively and significantly impact on repeat purchase. The variables of customer satisfaction significantly mediates the influence of experiential marketing towards repeat purchase.